Masjid selected mosques from the Islamic world - Azim Ab. Aziz (ATSA Architects, 2014)
"This pictorial book features a selection of the various mosque styles and designs that have been built throughtout the past 1435 years, ever since the formation of Islam by the Prophet Mujammad (PBUH) in the year 622." -- introduction